Self-efficacy of mathematics students‟ on e-learning during covid 19 pandemic - Endah Wulantina; Fertilia Ikashaum; Juitaning Mustika; Pika Merliza; Selvi Loviana; Nur Indah Rahmawati; Andianto Andianto (PROCEEDING UMSURABAYA, 2020)
Abstract.This research aims to describe the self-efficacy profile of students majoring inmathematics education in e-learning during the covid-19. The research subjects were 98 students of IAIN Metro mathematics semester 2, 4 and 6 who took part in e-learning. Students complete the self-efficacy questionnaire and interview guidelines. The results showed that 5.10% of students had very high self-efficacy, 28.57% high, 38.78% moderate, 21.43% low, and 6.12% very low. Furthermore, interviews were conducted with 6 students with high, medium and low self-efficacy criteria. The interview results show that students with high and moderate efficacy are feeling optimistic in carrying out online learning while students with low efficacy feel not optimistic in carrying out online learning. Their efforts have not been optimal due to several obstacles so they are not sure they can reach the learning target optimally. Students with high, moderate, and low self-efficacy have not been able to understand difficult lecture material through online learning. However, they always try to complete the task on time.